Gastropods Diversity on Rice Field Habitat at Different Altitude - Suartini, Ni Made; Sudatri, Ni Wayan (Metamorfosa: Journal of Biological Sciences; Vol 6 No 2 (2019)DO - 10.24843/metamorfosa.2019.v06.i02.p11, 2019)
Gastropods or often called snails, live in various habitats including in rice fields habitat. There are several species of rice field gastropods which are detrimental because they damage the plants but some can be utilized. The presence of rice field gastropods is influenced by environmental factors. Environmental factors are certainly different at different altitudes, so that it might affect the species of Gastropods that exist. This study aims to determine the diversity of Gastropods found on rice fields at different altitude. Gastropod sampling were carried out in several rice fields with different altitudes, that is under 100 m, 100 m to 300 m and above 300 m to 500 m above the sea level. Sampling were done by making a 1mx1m square placed in each corner of the rice field and in the middle of the rice field. In addition to the rice fields, samples were also taken from irrigation channels that irrigated the fields. Gastropods found were six species where Lymnaea rubiginosa and Digoniostoma truncatum were only found in rice fields in each location and Terebia granifera was only found in irrigation channels. Melanoides tuberculata, Melanoides maculata and Pomacea canaliculata were found in rice fields and irrigation channels. Locations I and II have a moderate diversity index (1,360 and 1,408) and location III is low (0,795).